Mapping the Cybersecurity Research through Bibliometric Analysis - Judijanto, Loso; Endrianto , Endrixs; Vandika, Arnes Yuli (West Science Information System and Technology, 2024)
This bibliometric analysis explores the evolution and global landscape of cybersecurity research from 2010 to 2024. Utilizing data sourced exclusively from Scopus and analyzed through VOSviewer, this study identifies significant trends, key themes, and the dynamics of international collaboration within the field. The findings reveal a notable increase in the volume of publications over the years, highlighting a shift from basic security measures towards the integration of advanced technologies such as artificial intelligence, the Internet of Things (IoT), and blockchain. The study also maps the dense network of international collaborations, with the United States, China, India, Germany, and the United Kingdom emerging as central nodes. This analysis not only reflects the increasing complexity of cyber threats but also the global effort to develop proactive and dynamic defense mechanisms. The results emphasize the need for continuous innovation and expanded international cooperation to address the challenges posed by rapidly evolving cyber threats. Future research should consider more interdisciplinary approaches and a wider range of databases to capture the full spectrum of cybersecurity research.